Breaking down barriers: promoting journals beyond the page with open access journal clubs - Angharad N. de Cates; Donncha Mullin; Lucy Stirland; Mariana Pinto da Costa; Derek Tracy (BJPsych Bulletin)
In 2020, during the early days of the COVID-19 pandemic, the British Journal of Psychiatry (BJPsych) established a series of free online teaching sessions called BJPsych Journal Clubs. Their educational purpose is two-fold: (a) to provide junior psychiatrists with a friendly but large-scale platform to evaluate and critically appraise recent articles published in the BJPsych and (b) to present new research findings in an open and accessible manner. In this paper, we discuss our framework, the challenges we encountered, how the original model is evolving based on feedback from trainees, and tips for success when delivering international online journal clubs.